2010
DOI: 10.1002/mrm.22605
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cardiac magnetic resonance imaging in the mouse using an eight‐channel array at 9.4 Tesla

Abstract: MRI has become an important tool to noninvasively assess global and regional cardiac function, infarct size, or myocardial blood flow in surgically or genetically modified mouse models of human heart disease. Constraints on scan time due to sensitivity to general anesthesia in hemodynamically compromised mice frequently limit the number of parameters available in one imaging session. Parallel imaging techniques to reduce acquisition times require coil arrays, which are technically challenging to design at ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Furthermore, time-volume analysis of the entire left ventricle showed that both diastole and systole have periods of 15–20ms, during which very little changes in left-ventricular volumes are observed (Fig. 6 of reference [12]). This is in line with early reports claiming that a temporal resolution of ~10 ms suffices to least determine end-diastole and end-systole with physiologically acceptable accuracy [1].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, time-volume analysis of the entire left ventricle showed that both diastole and systole have periods of 15–20ms, during which very little changes in left-ventricular volumes are observed (Fig. 6 of reference [12]). This is in line with early reports claiming that a temporal resolution of ~10 ms suffices to least determine end-diastole and end-systole with physiologically acceptable accuracy [1].…”
Section: Discussionmentioning
confidence: 99%
“…RF coils tailored for CMR are dedicated birdcage volume coils or surface coil arrays with the geometry adjusted to the size of a mice (25–35 mm inner diameter or 15–26 mm side length respectively) [2], [4], [5], [6], [7], [8], [10]. An emerging RF coil technology for MRI of small rodents is the cryo-cooling of RF coils, which reduces the electronic noise.…”
Section: Introductionmentioning
confidence: 99%
“…T1-mapping is commonly acquired with a sequence based on the look-locker method although some authors described SNAPSHOT-FLASH Inversion Recovery (SNAP-IR) [24,124] or variable flip angle [39] strategies for the acquisition. In mouse, the acquisition is mainly made in combination with a contrast agent, gadolinium [24,39,138] or manganese [8,77,87,88,168,169].…”
Section: T1 Mappingmentioning
confidence: 99%
“…Each element is associated with an independent radiofrequency pathway whose signals can be processed and combined together. A combination of such overlapping multiple receiver coil elements can be utilized to improve the signal-to-noise ratio and allows to speed up acquisitions as the number of spatial encoding steps can be decreased and conventional Fourier encoding reduced [40,124].…”
Section: Chemical Exchange Saturation Transfer (Cest) Mrimentioning
confidence: 99%